GenoType® HelicoDR test in comparison with histology and culture for Helicobacter pylori detection and identification of resistance mutations to clarithromycin and fluoroquinolones. Issue 6 (23rd October 2017) - Pastukh, Nina; Binyamin, Dana; On, Avi; Paritsky, Maya; Peretz, Avi
Abstract: Background: There are several methods for Helicobacter pylori infection diagnosis. Aim: The efficacies of three methods for H. pylori identification directly from a biopsy were compared: histology, culture, and molecular GenoType® HelicoDR test. Materials & Methods: Eighty‐five triplicates of stomach antrum biopsies were obtained during gastroscopy procedures for culture, histology, and molecular assay. In addition, we performed molecular identification of genes encoding resistance to clarithromycin and fluoroquinolones. Results: The results have shown that the most specific method with the highest number of positive specimens was by molecular kit, compared to culture and histology (94.3%, 77.1%, and 71.4%, respectively). There was a higher rate of resistance mutations to clarithromycin than to fluoroquinolones (68.26% vs 20%). The most common mutations for clarithromycin and fluoroquinolones resistance were found in alleles A2143G and N87K, respectively. The highest rate of positive specimens was identified by the molecular. Discussion: GenoType HelicoDR kit (94.3%), which has several advantages: direct identification, strain resistance characterization, mixture of genotypes detection, and no transport or storage limitations; thus, it is an excellent epidemiological screening tool. This work has demonstrated a lower resistance rate to fluoroquinolones; it is possible that in the investigated geographic area treatment with fluoroquinolones may be preferable to clarithromycin. GenoType® HelicoDR test eliminates the need for culture performance and susceptibility tests for several common antibiotic agents and enables optimal and specific antibiotic treatment adjustment. Conclusion: We recommend a combination of PCR assay and bacterial culture for a quick method of screening and more efficient identification of H. pylori strains and resistance patterns.